2016
DOI: 10.3138/jvme.1115-182r
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Analysis of Changing Student Confidence in an Online Shelter Medicine Course

Abstract: Maddie's Shelter Medicine Program at the University of Florida College of Veterinary Medicine offers comprehensive training in shelter medicine to veterinary students based on a set of core job skills identified by the Association of Shelter Veterinarians. In 2012, this program began teaching online distance education courses to students and practicing veterinarians worldwide who sought additional training in this newly recognized specialty area. Distance learning is a novel educational strategy in veterinary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…At present, with the intelligent development of big data technology, the data of home online physical education continues to grow exponentially with positive correlation, and the frequency of using home online physical education sharing platform also continues to grow. Faced with the situation of massive data of home online physical education, how to manage these massive data efficiently and explore the value of home online physical education has become the current problem faced by the home online physical education sharing platform [ 29 , 30 ]. To make the home online physical education sharing platform meet the needs of users and provide them with accurate services, it is obvious that traditional technology can no longer meet its application.…”
Section: Related Workmentioning
confidence: 99%
“…At present, with the intelligent development of big data technology, the data of home online physical education continues to grow exponentially with positive correlation, and the frequency of using home online physical education sharing platform also continues to grow. Faced with the situation of massive data of home online physical education, how to manage these massive data efficiently and explore the value of home online physical education has become the current problem faced by the home online physical education sharing platform [ 29 , 30 ]. To make the home online physical education sharing platform meet the needs of users and provide them with accurate services, it is obvious that traditional technology can no longer meet its application.…”
Section: Related Workmentioning
confidence: 99%
“…The body of evidence available assessing the impact of shelter specific and service-learning experiences on students is growing, further supporting its value in filling the gaps present in veterinary curriculums. Research has shown that experiences in shelter medicine can increase perceived self-confidence and preparedness for real-world challenges in the field post-graduation ( 31 ) and increase self-confidence in various shelter medicine themes ( 29 ). These experiences have also been shown to increase student rating of their ability to perform six shelter medicine tasks as well as ovariohysterectomy/ovariectomy (OVH/OE) and castration surgeries ( 31 ), and decreased surgery time ( 28 , 38 ) without a significant increase in complication rates ( 39 ).…”
Section: Introductionmentioning
confidence: 99%